POETRY BY RAINIS IN LATGALIAN - Senkāne, Olga (Via Latgalica, 2012)
Research „Poetry by Rainis in Latgalian” tried to establish impulse and reasons for publishing poetry by Rainis in Latgalian (original texts and renderings) using biographical method, but semiotic methods helped to analyze poetic means in poems written in Latgalian, revealing meaning of concept „Munu jaunu dīnu zeme” (Land of My Youth) in poem by Rainis and Latgalian culture.Poems by the most significant Latvian literature classic Rainis (1865–1929) in Latgalian can be divided into original texts („Sveicins latgališim”/Greetings to Latgalians), original texts with renderings into Latvian („Munu jaunu dīnu zeme”/Land of My Youth) and renderings from Latvian (at least 16 poems from selections: „Tālas noskaņas zilā vakarā”/Far off Echoes on a Blue Evening, 1903;„Tie, kas neaizmirst”/Those Who Don’t Forget, 1911; „Gals un sākums”/The End and the Beginning, 1912), besides, surely we can say author’s renderings are only „Munu jaunu dīnu zeme” (Land of My Youth) has well as all other texts from literally scientific and social magazine „Reits” (Morning), because Rainis had been one of the editors of this magazine. Poems by Rainis published in Latgalian in newspapers – „Drywa” (Cornfield), „Gaisma” (Light), „Latgolas Wòrds”(Latgalian Word), „Jaunò straume” (New Flow) – are possibly work of authors of these periodicals, considering significant differences in stylistics with magazine „Reits” (Morning) and earlier published poems by Rainis.Publishing of original texts and especially renderings in Latgalian press are mainly related to political activities of Rainis. But writing in Latgalian for Rainis also meant remembering his roots, remind of cultural wealth of native land and value; being a mediator in strengthening people’s unity and widening own supporters as well as the number of readers.In the discourse of Rainis personality and creative work „Munu jaunu dīnu zeme” (Land of My Youth) is 1) homeland, native nature and home of poet’s childhood and colorful impressions of his youth (Rainis father’s rented manor house (semi-manor house) in Zemgale and Latgale); 2) Rainis’ land of youth is writer’s „second homeland” – Latgale, its’ nature, people and language; 3) particular semi- manor house in Latgale – Jasmuiža.Origination of lyrical Me is emphasized in epos „Saules gadi” (Solar years) – Latgalian was born. From Rainis point of view Latgale is multinational keeper of authentic cultural values. About eight languages had been spoken in Rainis family. In Latgale, customs, folk-songs have been maintained untouched owing to certain isolation, historical and administrative separation from other parts – some kind of reserve effect. During years of his studies Rainis had intended to write a book about civilization untouched Latgale, but this intention left unimplemented.Memories about homeland motivated Rainis to write and render into Latgalian, but original texts in Latgalian – „Munu jaunu dīnu zeme” (Land of My Youth) and „Sveicins latgališam” (Greetings to Latgalian) – were written on behalf of stylistic searches in particular period of Rainis creative work; they chronologically incorporate with philosophical stage (according to Janīna Kursīte). In this time poet’s ontology forms, still balancing between allegory (transmission transparency, dichotomy) and symbol (polysemy and ambivalence) structures.In Rainis’ neo-romantic (1895–1904) and allegoric stage (1905–1909) poetry nature cycles project mainly society, not individual; only humanity will exist and revive eternally, precondition of immortality – death and birth of individual people.In the poetry of philosophical stage (starting from 1910) Rainis frequently lingered on individual’s immortality reflection, which he called search and recoveries. A person lives not only according to nature laws, but according to existence laws and dies according to these same laws. Symbol, most frequently mythologeme, becomes a sign of existence glimpse for Rainis; lyrical Me of Rainis is awaiting new experience, knowledge, and moral enlightenment. One has to search in order to find, and searching/cognition signal in his poems is a cycle of time and space (nature, society, human) and three- dimensional structure (outer world/history, individual/soul, philosophy/ being). In the poem „Munu jaunu dīnu zeme” (Land of My Youth) it is possible to follow 3 of the mentioned cycles development in peculiar symmetry: 1st , 6th stanzas are a framework of individual’s inner cycle – dream/illusion/ desideratum and interchange of wakefulness/ reality/ actuality; 2nd and 4th stanzas contain nature cycle allegory – nature in spring awakes from winter sleep; while 3rd and 5th stanzas are related to social processes, which are covered with day-and-night cycle. Basics of symmetry – state of sleep and awakening in all levels of previously mentioned time and space, creating triple parallelism.It is interesting how stanzas within a single cycle (1 and 6, 2 and 4, as well as 3 and 5) mutually relate: 1st , 2nd and 3rd stanzas contain reminiscences as symbolic sleep/dream abstractions of Rainis previously written poetry, while 4th , 5th and 6th stanzas specify something in nature, society and individual’s desires, dreams which have to wake up. Reminiscence carries out necessary associations for philosophical perceiving of functions time and space cycle, but especially – form and maintain transmission basics: historical (people’s destinies) – 3rd stanza, psychological (individual’s dreams, desires) – 1st stanza, philosophical (order of existence) – 2nd stanza.The above mentioned allows stating that poem created by Rainis in Latgalian „Munu jaunu dīnu zeme” (Land of My Youth) indeed incorporates into Rainis creative work philosophic stage, where allegory as a supplementary tool and symbol as a dominant harmonically gets along with poet’s revelation of ontological sense.Poem „Sveicins latgališim” (Greetings to Latgalians) has one addressee – a Latgalian, new reader of the newspaper. The text is artistically created on the allegoric stage standards of Rainis creative work – here features of one cycle (human in society) are present. Social cycle stages revealed in the poem are parting/uniting, hatred/love, old life/new life, celebrations/work.Artistic structure of poems in Latgalian indicates on dominance of allegory or symbol in time and space. Cycle has a special meaning in reflection of existence order.